Ethnic Identity of Young People in Poly-Ethnic Environment - E Ju Chebotareva (Peoples' Friendship University of Russia (RUDN University), 2012)
The paper presents the analysis of the ethnic identity types among the young people in the polyethnic environment. It was found relations between the ethnic identity and the level of the intercultural competence, the strategies of the inter-ethnic interaction, difficulties in the cross-cultural interaction, and the personality traits.